If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -1b = b + 4 + -3b Reorder the terms: -3 + -1b = 4 + b + -3b Combine like terms: b + -3b = -2b -3 + -1b = 4 + -2b Solving -3 + -1b = 4 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. -3 + -1b + 2b = 4 + -2b + 2b Combine like terms: -1b + 2b = 1b -3 + 1b = 4 + -2b + 2b Combine like terms: -2b + 2b = 0 -3 + 1b = 4 + 0 -3 + 1b = 4 Add '3' to each side of the equation. -3 + 3 + 1b = 4 + 3 Combine like terms: -3 + 3 = 0 0 + 1b = 4 + 3 1b = 4 + 3 Combine like terms: 4 + 3 = 7 1b = 7 Divide each side by '1'. b = 7 Simplifying b = 7
| 28-5e=40-6e | | 3x-5y+11=4(5x-2y) | | 5x+y=16 | | -3-4(5x-2)-11= | | 5(6)+4y=8 | | 5(4)+4y=8 | | 5(2)+4y=8 | | 5(0)+4y=8 | | P(x)=5x^5-6x^4-24x^3+20x^2+7x-2 | | 5(-1)+4y=8 | | 49=10p-3p | | 5(-4)+4y=8 | | 7b+17=4b+32 | | 3x^2+10x-3=0 | | 15+2(3x-5)-7= | | 2k+3+k-11=-2k+4k | | -5*3x=-15 | | 3p+15=60-20 | | 2(4)-0.333333333333333y=4 | | 1.5=3.3y | | 2(1)-0.333333333333333y=4 | | 6-3(5x+2)=4(1-x) | | r+r+8=100 | | 2(3)-0.333333333333333y=4 | | 8*6=8*(3+3) | | r+r+16=100 | | 86=2(-5n+3) | | (2+3)x+(10-4)= | | 2k+3+k-11=2k+4k | | 2(-1)-0.333333333333333y=4 | | -5x^3=-15 | | -7.24q=17.014 |